Three Is a Crowd? Podemos, Ciudadanos, and Vox: The End of Bipartisanship in Spain - Rama, José; Cordero, Guillermo; Zagórski, Piotr (Frontiers in Political Science, 2021)
The traditional Spanish imperfect bipartisanship and the alternation in power that emerged in the early 80s between the center-left PSOE and the conservative PP have shifted towards a multiparty system after the emergence of three new parties. At first, as a result of the economic and political representation crises, Podemos (We Can) emerged at the 2014 European Parliament elections. This left-wing populist party managed to grow rapidly among the dissatisfied voters, reaching the third electoral position in the 2015 general elections. In the same contest, the liberal center party Ciudadanos (Citizens) became the fourth political force boosted, among other reasons, by notorious corruption scandals involving high-rank PP’s officials and the process of secession in Catalonia. Finally, driven by the same secession process and thanks to the removal from the office of PP’s Prime Minister after a motion of no confidence, the support for the populist radical right Vox also experienced a boost, winning 15 percent of the seats in Parliament in the general elections of November 2019. In this research, we describe the contexts which facilitated the irruptions of these new parties, analyze their impact on the Spanish party system, and study their current voters’ profiles.